2019
DOI: 10.3390/agronomy9040200
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physiological Responses and Root Distribution Patterns of Ratooning Ability and Yield of the Second Ratoon Cane in Sugarcane Elite Clones

Abstract: Poor ratooning ability for sugarcane can limit crop productivity and profitability of sugarcane growers. The objective of this study was to determine the association of physiological responses and root distribution patterns on the yield of the second ratoon cane, and the relationships between these traits. Seventeen sugarcane genotypes were planted in a randomized complete block design with four replications. The second ratoon crop was evaluated for germination percentage, cane yield, Soil Plant Analysis Devel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…In addition to the agronomic and environmental factors considered roughly the same in a study, the RA of cotton is also affected by the genotype, crop age, and their interactions. For all the traits of ratoon cotton studied by Komala et al (2018d) , there were significant differences in RA among the genotypes evaluated, and similar phenomena were reported for ratoon sugarcane ( Ogunniyan et al, 2018 ; Chumphu et al, 2019 ). Within the same cotton genotype, there were significant differences in boll number per plant, boll weight, lint index, and seed cotton yield per plant between the PCs and the RCs ( Komala et al, 2018d ).…”
Section: Evaluation Of the Ra Of Cottonsupporting
confidence: 78%
See 1 more Smart Citation
“…In addition to the agronomic and environmental factors considered roughly the same in a study, the RA of cotton is also affected by the genotype, crop age, and their interactions. For all the traits of ratoon cotton studied by Komala et al (2018d) , there were significant differences in RA among the genotypes evaluated, and similar phenomena were reported for ratoon sugarcane ( Ogunniyan et al, 2018 ; Chumphu et al, 2019 ). Within the same cotton genotype, there were significant differences in boll number per plant, boll weight, lint index, and seed cotton yield per plant between the PCs and the RCs ( Komala et al, 2018d ).…”
Section: Evaluation Of the Ra Of Cottonsupporting
confidence: 78%
“…The interaction between genotype and crop age significantly affected all the traits studied, which indicates that hybrid performance differs during different cropping cycles. Studies have shown that the interaction between genotype and crop age is highly important to yield its contributing traits ( Ahmed et al, 2016 ; Komala et al, 2018d ; Chumphu et al, 2019 ). Therefore, RA j = RC j /PC can be used to calculate the RA of crops at different ages (j).…”
Section: Evaluation Of the Ra Of Cottonmentioning
confidence: 99%
“…Leaf area index (LAI) is effective to evaluate the end yield, and the highest values during the development cycle would be related to the higher-end cane and sugar yields (Leme et al, 1984 andReis et al, 2013). Some physiological traits were directly or indirectly associated with crop growth and yield (Chumphu et al, 2019 andSilvia et al, 2007). Figure 5) showed significant differences for broad-sense heritability estimates (h 2 ) among all studied traits in both crops.…”
Section: Correlations Between Physiological Charactersmentioning
confidence: 99%
“…Sugarcane in the Australian tropics is typically harvested annually with four or more ratoon crops grown before cane is removed [2]. While ratoon crops can have lower yields than plant cane crops, the cost of production is typically lower [3]. However, the continual production of sugarcane in the same field over time has led to observations of yield decline, which appears to be related to a decline in soil health and build-up of pathogens associated with the sugarcane monoculture [4].…”
Section: Introductionmentioning
confidence: 99%
“…One potential management option to address yield decline in sugarcane is the introduction of rotation crops in the fallow period between plough-out and replanting of subsequent cane crops [5]. Potential benefits of rotation crops or cover crops in the summer wet season in the Australian tropics during the sugarcane fallow period include improved groundcover and protection against erosion, reduced NO 3 − leaching, increased carbon (C) inputs into soils and improvements in soil biological populations related to cane health. A number of studies have investigated short-term cover crops or longer-term break crops over 9-42 months during the sugarcane cycle [2,6], but most have focussed on fallow legume crops to break the monocot monoculture and improve soil microbial populations related to cane health [5].…”
Section: Introductionmentioning
confidence: 99%